Pengaruh Kurangnya Pengetahuan Dan Kebiasaan Menabung Terhadap Pengelolaan Keuangan Pribadi di Kalangan Pelajar - Saidatul Mardiyah (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
This Real Work Lecture (KKN) program was carried out by students of the Muhammadiyah University of North Sumatra in Telaga Pure Village, Langkat Regency. This activity focuses on observing and analyzing the influence of lack of knowledge and saving habits on personal financial management among students. Through this service, students help and educate the public on the importance of knowing and getting used to saving from an early age among students. The main aim of this activity is to increase awareness and knowledge as well as the habit of saving which will have a long-term impact on individuals who implement this. This program consists of several activities, outreach and mutual cooperation activities to maintain a clean environment. The results of this activity show that the impact of the lack of this is still negative and we will continue to try to find a solution. Apart from that, students also succeeded in educating and socializing the importance of knowledge and the habit of saving for personal finances among students.